2018
DOI: 10.23938/assn.0370
|View full text |Cite
|
Sign up to set email alerts
|

Cavernous hemangioma of the nasal bones: a case report

Abstract: REsUMEnLos hemangiomas cavernosos representan menos del 1% de todos los tumores óseos, siendo las vértebras y el cráneo las localizaciones más habituales. Estos tumores son extremadamente raros en los huesos de la nariz, con muy pocos casos publicados en la literatura médica, descritos en cornetes, vómer, huesos propios o lámina perpendicular del etmoides. Suelen presentarse como una lesión tumoral que crece con el tiempo, implicando al hueso e incluso a tejidos blandos, pudiendo causar complicaciones como obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The etiology of nasal bone haemangioma is unknown, but previous trauma could act as a predisposing factor 16 . The patient in our case had no history of trauma to the nasal or head area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The etiology of nasal bone haemangioma is unknown, but previous trauma could act as a predisposing factor 16 . The patient in our case had no history of trauma to the nasal or head area.…”
Section: Discussionmentioning
confidence: 99%
“…The patient in our case had no history of trauma to the nasal or head area. Also, it has been observed that it affects women more often and the average age of presentation is 40 years 16 . Our patient is a boy, in the second decade of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation